Flurbiprofen and Its Derivatives of Many Therapeutic Uses-A Recent Report - Kumar, Praveen; Kumar Pathak, Pawan; Kumar Gupta, Vikram; Srivastava, B.K.; Kushwaha, B.S. (Asian Journal of Chemistry, 2012)
Flurbiprofen has shown an excellent therapeutic action against many diseases and has been reported to possess antiinflammatory, analgesic, antipyretic, antimicrobial, antipuritic, antithrombotic, antinociceptive, antitumour and radioprotective activities. The derivatives of flurbiprofen have been reported to contribute significantly in controlling various diseases. In this context, the present report deals with the summary of therapeutic uses of flurbiprofen and its various combinations that play an important role in controlling painful and deadly diseases along with reducing serious side effects caused by the usual medical treatment.